Prevalence of the E318K MITF germline mutation in Italian melanoma patients: associations with histological subtypes and family cancer history. (10th December 2012) - Ghiorzo, P.; Pastorino, L.; Queirolo, P.; Bruno, W.; Tibiletti, M. G.; Nasti, S.; Andreotti, V.; ,; Paillerets, B. Bressac‐de; Bianchi Scarrà, G.
Summary: A French and an Australian study have recently identified a rare germline functional variant in the microphthalmia‐associated transcription factor (MITF) (E318K) that predisposes to familial and sporadic melanoma and to renal cell carcinoma (RCC), showing a new link between two tumour types with different risk factors and between deregulated sumoylation and cancer. The aim of this study was to test the prevalence of the MITF E318K mutation in 667 Italian melanoma patients. We observed significant associations between histological subtypes and family cancer history. Carriers exhibited a nearly threefold higher risk of developing melanoma compared with controls. Carriers were also more likely to have developed multiple primary melanomas (6.40‐fold), compared with wt patients. Carriers with a personal and/or family history of pancreatic cancer and kidney cancer had a nearly 31‐ and eightfold higher risk of developing melanoma compared with wt patients. Our findings further support MITF as a medium‐penetrance melanoma susceptibility gene, highlight a potential association with histological subtypes and suggest that MITF may predispose to pancreatic cancer.